Crouching tigers hidden dragons: on the myth of the two birth signs. Issue 2 (3rd May 2016) - Hung, Chih-Hsing; Yang, Der-Yuan; Lee, Yi-Hsi
ABSTRACT: Sensational reports on the number of newborn in the years of tiger and dragon have aroused great concerns among certain governments. Substantial social cost will be incurred if any age group diminishes or multiplies out of proportion. This article clarifies the facts concealed underneath those breathtaking anecdotes. The statistics of Hong Kong, Singapore and Taiwan, where people have strong passion for the birth sign dragon and distaste for tiger, shows that there are neither shrinking tiger nor bulging dragon cohorts for the newborn or the whole population.